A problem-solving perspective on strategies for appropriating environmental value – some implications from considering institutional solutions to social dilemmas. (1st January 2012) - Linder, Marcus
The paper outlines a framework of value creation and appropriation strategies available to firms that address environmental problems. It does so by utilising the idea that valuable problem-solution pairs correspond to opportunities and by describing why many environmental problems are 'valuable' problems as defined by the problem-solving perspective of the firm. Considering social dilemmas as the main hurdle for the appropriation of environmental value by firms, the paper derives four appropriation strategies for environmental innovations by drawing on the literature on economic institutions. The appropriation strategies are labelled eco-lean, eco-branding, eco-lobbyism and eco-transaction design.